A expressão de tempo em enunciações produzidas por sujeitos com afasia - Corrêa, Heloisa Scherer (2024)
The disorder of language known as aphasia can affect communication in different aspects. The subject with aphasia usually presents difficulties in processing some linguistic elements, such as syntactic organization, lexical choices, and vocabulary restrictions, among other issues in expression and comprehension, which affect interlocution and social interaction. As it is understood that interlocution is part of human nature, humans are conceived as indissociable from the language that constitutes them and, under this perspective of Benvenistian inspiration, it is proposed the study of oral enunciations produced by subjects with aphasia participating in an Interdisciplinary Group of Coexistence at the Universidade Federal de Santa Maria, reflecting a singular social reality concerning the language in use. The theoretical background is composed of the enunciative perspective by Émile Benveniste, the typology of aphasia according to Roman Jakobson, which is addressed especially in the article Two Aspects of Language and Two Types of Aphasic Disturbances, as well as the notion of gesture that, associated to the aphasias, expresses meanings sometimes verbally precluded, constituting singular signification to promote interlocution and hence produce senses. The objectives are to identify and assess time indices in oral enunciations produced by subjects with aphasia, considering Jakobson’s typology of aphasia - disorder of contiguity and similarity. This is a qualitative research that focuses on particularities of the aphasias in the oral enunciative act and, in this respect, enunciative facts produced in six enunciative situations in which five subjects with aphasia participated were selected as corpus. As a result, the indicating elements of the category of time are manifested in the oral enunciations of the subjects with aphasia as presenting alterations consonant with the Jakobsonian classification: in the disorder of similarity, a common repetition of words related to time and the maintenance of the use of verbs in the present tense; while in the disorder of contiguity, the maintenance of verbs in the present and past tenses, the enunciation of numbers with dates, the enunciation of the days of the month, and the usual absence of enunciations that indicate the days of the week and the months of the year were observed. Moreover, there is the employment of gestures in greater frequency by subjects with disorder of similarity compared to the other participants. As can be observed, the application of Jakobson’s proposal on aphasias allows one to comprehend particularities of language, as for this study, regarding the category of time, evidencing the use of time indicators in disorders of similarity and contiguity.